Some morphological differences between opposite sides of the body of elite Eropean junior badminton players - Petrinovic, L.; Stefan, L.; Munivrana, G. (Acta Kinesiologica, 2015)
The aim of the study was to determine some morphological differences between sides of body (dominant versus non-dominant) of elite junior badminton players. The sample consisted of 85 high profile junior badminton players from Europe that have played on European Junior Circuit. They were gauged with 12 morphological measures aiming to gain some basic information regarding the players` morphological status and to establish relations between dominant and non-dominant side of the body, by comparing circumferences of limbs on both sides. The results obtained by the study have established significant (forearm and upper leg; p= 0,00) or non-significant (p=0,11), but nevertheless visible (30,49±16,96 opposed to 27,51±2,42) differences (upper arm) between circumferences of limbs of badminton players on opposite sides of their bodies, with higher values shown on the dominant side. The only exception of the rule has been shown on the lower leg circumference (36,58±2,58 opposed to 38,09±12,57). Badminton players, due to unilaterality of the sport, are predisposed to develop some morphological imbalances, which can both; increase potential risk of injuries and negatively influence players` performances in the game. Therefore, additional bilateral physical exercises that would help diminish some negative consequences of frequent and intensive badminton training and would enable symmetrical development of young badminton players`, should be implemented in their training.